Manipulation under anaesthesia versus ultrasound-guided neuronal block for primary frozen shoulder: short-term outcomes and comparative analysis - Mert, Murat; Ince, Abdullah Yener; Caglar, Sibel (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the short-term clinical outcomes of manipulation under general anesthesia versus ultrasound-guided neuronal block in patients with primary frozen shoulder. Method: The retrospective, single-center study was conducted at the Department of Orthopedics, Yeniyuzyil University, Istanbul, Turkiye, from April 10 to May 10, 2021, and comprised data from January 1, 2010, to December 31, 2020, of patients having frozen shoulder. They were divided into manipulation under general anaesthesia group A, manipulation under ultrasound-guided neuronal block group B, and control group C that received self-administered physical rehabilitation exercises. Preoperative passive range of motion and pain scores were recorded, and postoperative assessments were conducted at two different follow-up points. Data was analysed using SPSS 23. Results: Of the 54 patients, there were 18(33.3%) in group A with mean age 43.88±12.48 years, 18(33.3%) in group B with mean age 48.67±13.57 years, and 18(33.3%) in group C with mean age 50.68±11.89 years. Each group had 10(55.5%) females and 8(44.4%) males (p>0.05). Groups A and B showed significant improvements compared to baseline measures (p<0.05). Group A demonstrated greater improvement in flexion immediately after the intervention (p<0.05), while group B showed superiority in abduction, external rotation and pain relief one week after the intervention (p<0.05). No major complications were observed in any group. Conclusion: Manipulation under general anaesthesia and ultrasound-guided neuronal block were both effective treatment options for primary frozen shoulder, with potential advantages in specific outcomes. Key Words: Frozen shoulder, Adhesive capsulitis, Manipulation, Anaesthesia, Ultrasound-guided, Nerve block, Treatment.